Hello English App for Online Learning during the Pandemic: Does it Enhance the Students’ English Vocabulary Development? - Sudarmaji, Imam; Forsia, Lastry; Siregar, Indah Permata Sari; Yusuf, Danu (Universitas Lancang Kuning, 2022)
The Covid-19 Pandemic made it almost impossible for the students learn face-to-face. The demand of technology for learning online is needed in such situation. The writers chose Hello English App to find out the enhancement of the app on students’ English vocabulary development and the perceptions at the seven-grade level of private junior high school in Indonesia in academic year 2020/2021. This quantitative study with quasi-experimental design involving seventh-grade students. The researcher provided a multiple-choice test consisting of 30 students in experimental and control class respectively through pre-test, treatment and post-test. The researcher employed statistical calculation of the t-test formula with 5% significance level using SPSS 22 based on the score collected from the students’ pre-test and post-test results. It was found out that, the mean score of a post-test in the experimental class was significantly higher than the conventional class. The result of t-test indicated that Hello English has a significance impact on the development of students’ English words. Meanwhile, the questionnaire results showed that most students agreed (>80%) that the Hello English App can assist them in English learning, particularly English words They felt satisfied and enjoyed the learning process when they employed the Hello English App to acquire English words as well. As a conclusion, the app is applicable in mastering students’ English words. It is recommended for learners and teachers as an alternative way during the Pandemic. The result from this research is essential. However, limited time during treatment and participants could not make the findings generalized.